Development of Religious Character in the Learning of Moral Creed in Madrasah Ibtidaiyah - Yudiyanto, Mohamad; Hani, Umi; Ramdani, Peri; Nurcahyati, Sri (Peneliti.net, 2023)
Religious character includes high moral integrity, in which the individual acts by the religious values he adheres to, both in relationship with God and with fellow human beings. The purpose of this study is to analyze the development of religious character in learning Akidah Akhlak in MI. The research method used is library research with a qualitative research approach. The results of the study showed, through learning Akidah Akhlak, MI students were introduced to the basic teachings of Islam, such as tawhid, treatises, and the afterlife. This helps strengthen students' religious awareness and strengthen their Islamic identity. These subjects help students to internalize Islamic religious values in their daily lives. They are taught to be individuals who obey God, have noble morals, and are responsible in their behavior. Learning Akidah Akhlak helps students understand and practice the moral and ethical values taught in Islam, such as honesty, justice, and compassion